Iranian Merchants as a Religious Community in Late Ottoman Istanbul - Abdülkadir Yeler (Journal of Economy Culture and Society)
Long-term peace between the Ottoman Empire and Iran provided an opportunity for Iranians to carry out various activities, especially trade, in the Ottoman Empire. Istanbul, the link between Asia and Europe, had become a point of interest to Iranian merchants as early as the 18th century, but it was particularly during the second half of the 19th century that one could speak of a well-organized Iranian community at the heart of the social and commercial life of the city. This community, formed mainly by merchants, was also a religious community belonging to the Shia sect, which enabled them to act together and form an organized community in Ottoman Istanbul, the population of which consisted mainly of Sunni Muslims. The combination of religious, cultural, social, and other practices of the Iranian merchants had brought an institutionalization along with it, and thus memories were created that would leave a legacy in the cultural history of Istanbul. Through an investigation of state archives in Turkey, this study aims to explore the story of Iranian merchants during the 19th century Ottoman period in Istanbul, focusing on their commercial, social and religious lives. The findings of the study shed light on the institutionalization of Iranian merchants as a close-knit community based on their commitment to sect-based practices.